Physiological determinants of cross-country ski racing performance - Mahood, N. V.; Kenefick, R. W.; Kertzer, R.; Quinn, T. J. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: Previous laboratory testing has identified the importance of upper-body aerobic and anaerobic power to cross-country skiing performance. The purpose of this investigation was to extend laboratory research into a field setting to identify predictors of performance through ski-specific testing. METHODS: Thirteen male collegiate skiers performed three field-testing sessions on roller skis to establish lactate threshold (LT) and ski economy (ECON) and maximal oxygen uptake (SK VO2max) and a 1-km double-pole time trial (UBTT) to determine peak upper-body oxygen uptake (UB VO2). As a measure of skiing performance, the subjects performed a 10-km skating time trial (TT) and were ranked according to competitive season performance (RANK). RESULTS: Significant correlations (P < 0.05) were found between SK VO2max, LT VO2, UB VO2, and RANK (r = -0.66 to -0.84) and TT time (r = -0.74 to -0.79), as well as ECON to RANK (r = 0.57) and TT time (r = 0.68). Time to complete the UBTT (UB time) exhibited the strongest correlation to both RANK (r = 0.95) and TT time (r = 0.92). Multiple regression analyses revealed that UB time was the best predictor of RANK and TT time, as demonstrated by the significant beta values (0.77, P < 0.001, and 0.79, P < 0.001, respectively). The importance of the UB component was further seen in that UB time was still the best predictor of performance when the subjects were divided into two distinct groups of greater and lesser competitive ability. CONCLUSIONS: These findings identify the importance of the upper body component to cross-country skiing performance, suggesting a need to focus on upper-body conditioning within a well-rounded endurance training program. Additionally, the UBTT exhibits potential as a simple field test to predict cross-country skiing performance over more sophisticated and costly laboratory and field testing.